2012
DOI: 10.11005/jbm.2012.19.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bisphenol A Concentration in Postmenopausal Women with Osteoporosis

Abstract: ObjectivesBishphenol A (BPA) is a representative endocrine disruptor and is also known as a xenoestrogen. The objective of the present study is to investigate how many patients are exposed to BPA and to analyze the relationships between serum BPA concentration, bone mineral density (BMD) and biochemical bone markers in postmenopausal women with osteoporosis.MethodsTotal 51 patients were enrolled for measuring BPA and clinical variables including BMD and bone markers. The relationship between BPA and clinical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…Two studies (65,73) observed positive correlations between serum BPA levels and BMI. The other four studies did not observe an association between serum BPA concentrations and BMI (68,(77)(78)(79) . Only one of these studies reported adjusting for potential confounders, such as age or health status (79) .…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Two studies (65,73) observed positive correlations between serum BPA levels and BMI. The other four studies did not observe an association between serum BPA concentrations and BMI (68,(77)(78)(79) . Only one of these studies reported adjusting for potential confounders, such as age or health status (79) .…”
Section: Resultsmentioning
confidence: 83%
“…For six of the articles, body composition (BMI, WC and/or weight) was the primary outcome of interest (62)(63)(64)67,71,74) . Seven studies included only women (65,67,69,73,74,77,78) , nine of the studies were in general adult populations (62)(63)(64)66,67,70,71,75,76) , one study included men and women ≥60 years (72) and another included only 70-year-old men and women (79) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the severe osteoporosis results in a wide low back pain and thoracodorsal pain, and then bringing difficulties in diagnosing painful vertebrae through a general physical examination for many patients. X-ray and CT play an important role in diagnosing the fractured vertebral body, but they cannot diagnose the fractured vertebral body without obvious morphological changes and cannot clearly distinguish the differences between the painful vertebrae and old fractured vertebral body [11,12]. MRI is a type of tomography which uses the physical phenomenon of magnetic resonance to obtain the electromagnetic signal from the human body, and reconstruct the human body structure.…”
Section: Resultsmentioning
confidence: 99%